Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 519 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Vampyressa pusilla (Wagner, 1843)", "HasGeospatialIssue is false", "HasCoordinate is true" ] } The dataset includes 519 records from 28 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0001460-150922153815467/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences